SURFACE AREA EVALUATION OF MOSUL DAM LAKE USING SATELLITE IMAGERY TECHNIQUE - Mahmod, H Mahir; Abbood, Imad Shakir; Hanoon, Ammar Nasiri (MATTER: International Journal of Science and Technology, 2020)
Due to water resources such as Tigris and Euphrates rivers, tributaries branches, marshlands and lakes, Iraq is considered, generally in the world and especially in Middle East, as one of the richest countries. These resources are already affected by the consequences of climate change increasingly. One of the most vital projects in Iraq is Mosul Dam (in the northern of Iraq), thus, Mosul Dam lake (MDL), in term of surface area, was observed and studied during the prior 35 years (1984-2019) to detect the effects of historical climate changes on surface area. Satellite data of Landsat has been used in this study based on route 170 and line 35. Best and cloud-free satellite images were downloaded from US Geological Survey. Eventually, ArcGIS technique was used to process and analyze the satellite images. The result displayed that average surface area and parameter of study area was about 242 km2 and 432 km consecutively. Relationship between surface area (A) and parameter (P) of study area has been generated and formulated. Furthermore, the correlation coefficient between surface area and parameter was about 71%. Coefficient of variance (COV) was found also to be about 0.271. Minimum surface area and parameter of study area were recorded in Sep. 2018 of about 171 km2 and 350 km respectively regardless the dates before the operating Mosul Dam, whereas, maximum A and P lake was found to be 337 km2 and 664 km in April,1994 respectively. The analysis showed that the exponential curve representing the best relationship between P and A.